Modelling and stability analysis of aircraft power systems - Areerak, Kongpan (2009)
The more-electric aircraft concept is a major trend in aircraft electrical power system engineering and results in an increase in electrical loads based on power electronic converters and motor drive systems. Unfortunately, power electronic driven loads often behave as constant power loads having the small-signal negative impedance that can significantly degrade the power system stability margin. Therefore, the stability issue of aircraft power systems is of great importance. The research of the thesis deals with the modelling and stability analysis of an aircraft power system. The aircraft power system architecture considered in the thesis is based on the More Open Electrical Technologies (MOET) aircraft power system with one generator as only a single generator can be connected to a system at any one time. The small-signal stability analysis is used with the system dynamic model derived from the dq modelling method under the assumption that the aircraft power system operating point does not change rapidly during normal operation mode. The linearization technique using the first order terms of a Taylor expansion is used so as to achieve a set of linear models around an equilibrium point for a small-signal stability study. The thesis presents the development of effective models capable of representing the electrical power system dynamic behaviour for stability studies. The proposed model can be used to predict the instability point for variations in operating points and/or system parameters. Agreement between the theoretical estimation, simulation, and experimental results for a simple system are achieved that ranges from acceptable to very good. Finally, the subsystem models described in the thesis can be interconnected in an algorithmic way that is representative of a more generalized aircraft power system model. The generalized model is also applied to a more complex and realistic aircraft power system with simulation validations for thorough investigations of aircraft power system stability. This model may be considered as a powerful and flexible stability analysis tool to analyse the complex multi-converter electrical power systems.